Parental Mediation of Children’s Risky Experiences with Digital Media - James, Patience Ada; Kur, Jude Terna (The Journal of Society and Media, 2020)
Children’s use of digital media is associated with risky experiences, a situation warranting parental mediation. Previous studies on parental mediation of children’s digital media use, conducted in advanced countries in Europe, America and Asia with rich experiences of children’s digital media use, examined only specific risks and rarely focused on effectiveness of the mediation strategies adopted. The present study investigated parental mediation of children’s risky experiences with digital media in an African setting, focused on four categories of risks and measured the effectiveness of adopted mediation strategies. Objectives of the study were to identify the mediation strategies parents applied in mediating risks (conduct, content, contact and commercial) encountered by children in the use of digital media, and ascertain the consequences of the mediation strategies. The study, a survey, used a sample of 265 parents drawn from a population 863 academic and non-academic staff members of Ibrahim Badamasi Babangida University, Lapai, Niger State, Nigeria. Parental Knowledge and Intervention in Children’s Risky Experiences with Digital Media Questionnaire (PKICREDMQ), designed by the researchers, and successfully scaled through validity and reliability tests, was used to generate data. Findings revealed that the parents adopted mainly two mediation strategies – restrictive and active